Answer :

X = (m1x2 + m2x1)/ m1 + m2


= (1 × 6 + 1x (– 2)/1 + 1


= (6 – 2) /2


= 4/2 = 2


Y = (m1y2 + m2y1)/ m1 + m2


= (1x 3 + 1x 9)/2


= (3 + 9)/2


= 12 / 2 = 6


C(2,6)


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses